COMPARISON OF THE CONCEPTS OF THE BUSINESS SEGMENT AND THE CENTER OF RESPONSIBILITY USED IN THE MANAGEMENT SYSTEM OF RETAIL ENTERPRISES - Mansurov, Shahzod; Mamatov , Farrukh; Fazliddin, Mukhtorov (Science technology&Digital finance, 2023)
The article is devoted to the study of approaches to the preparation of segment reporting at retail enterprises. The most correct principles of segmentation are revealed.